Apolipoprotein E Enhances MicroRNA-146a in Monocytes and Macrophages to Suppress Nuclear Factor-κB–Driven Inflammation and Atherosclerosis. Issue 1 (19th June 2015) - Li, Kang; Ching, Daniel; Luk, Fu Sang; Raffai, Robert L.
Abstract : Rationale: : Apolipoprotein E (apoE) exerts anti-inflammatory properties that protect against atherosclerosis and other inflammatory diseases. However, mechanisms by which apoE suppresses the cellular activation of leukocytes commonly associated with atherosclerosis remain incompletely understood. Objective: : To test the hypothesis that apoE suppresses inflammation and atherosclerosis by regulating cellular microRNA levels in these leukocytes. Methods and Results: : An assessment of apoE expression among such leukocyte subsets in wild-type mice revealed that only macrophages and monocytes express apoE abundantly. An absence of apoE expression in macrophages and monocytes resulted in enhanced nuclear factor-κB signaling and an exaggerated inflammatory response on stimulation with lipopolysaccharide. This correlated with reduced levels of microRNA-146a, a critical negative regulator of nuclear factor-κB signaling. Ectopic apoE expression in Apoe –/– macrophages and monocytes raised miR-146a levels, whereas its silencing in wild-type cells had an opposite effect. Mechanistically, apoE increased the expression of transcription factor purine-rich PU-box–binding protein 1, which raised levels of pri-miR-146 transcripts, demonstrating that apoE exerts transcriptional control over miR-146a. In vivo, even a small amount of apoE expression in macrophages and monocytes of hypomorphic apoE mice led to increased miR-146a levels, and inhibited macrophage proinflammatory responses, Ly-6C high monocytosis, and atherosclerosis in the settings of hyperlipidemia. Accordingly, cellular enrichment of miR-146a through the systemic delivery of miR-146a mimetics in Apoe –/– Ldlr –/– and Ldlr –/– mice attenuated monocyte/macrophage activation and atherosclerosis in the absence of plasma lipid reduction. Conclusions: : Our data demonstrate that cellular apoE expression suppresses nuclear factor-κB–mediated inflammation and atherosclerosis by enhancing miR-146a levels in monocytes and macrophages. Abstract : Supplemental Digital Content is available in the text.